Media, Journalism and Disaster Communities
XV, 247 p. 9 illus.
Keywords: This book illuminates the concept of disaster communities through a series of international case studies. It offers an eclectic overview of how different forms of media and journalism contribute to our understanding of the lived experiences of communities at risk from, affected by, and recovering from disaster. This collection considers the different forms of media and journalism produced by and for communities and how they may recognise and speak to the different notions of community that emerge in disaster contexts – including vulnerabilities and consequences that arise from environmental destruction and geophysical hazards, the insecurity created by armed conflict and limitations on journalistic freedoms, and result from human (in)action and humanitarian crises.